Legal And Ethical Debate Concerning Escorts On Public Roads: A Comparative Case Study - Sebastian, Muhammad Vino; Akmala, Ali Faza; Torin, Muhammad Farrel Arrizky (Dinasti Research, 2025)
Abstract. This research aims to comprehensively analyze the conflict between the implementation of Article 134 of Law No. 22 of 2009 (UU LLAJ) regarding priority rights and the fundamental principle of equality among road users. This conflict is triggered by the phenomenon of official escorts that consistently spark public controversy and ethical debate, often exacerbated by viral displays of arrogance. Using a normative-comparative approach, the study dissects how the loose interpretation of priority rights creates discretionary loopholes that are prone to abuse, consequently eroding public trust in law enforcement. The discussion is further strengthened by a comparative study of escort practices applying a Risk-Based Approach in other countries, and the case study of De Facto Diplomatic Priority (Ambassadors). This comparison is crucial to clearly distinguish between functional priority (based on real urgency) and status/ceremonial priority. The conclusion affirms the urgent need to review and reform the UU LLAJ and its technical regulations by adopting Objective Risk-Based Criteria to shift the escort paradigm from status-based to functional-urgency based, thereby restoring the public's sense of justice and trust.